Studi Penentuan Nilai Koefisien Pengaliran DAS Batang Arau di Kota Padang - Fitri Handayani -; Rahmania Hardiyenti -; Indra Agus -; Sadtim - -; Hartati - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2020)
Batang Arau river is located 0048” up to 0056” SL (South Latitude) and on 100021” up to 100033” LE (Longitutede East), and upstream part water catcment area it is cover 30,90 km2 area. The above said catchment area is a region consist of densely .populated and also dominated by vegetation of natural forest, protected forest, people’s forest, mixed forest, farm, recefield and yard. Based on site observation, most of the forest has changed become residant farms and settlement. This condition can be shown by land use map and change of runoff which was change from year to year. With this land use change however will also affecty changing of runoff coefficient. The goals of this study is to get flow coefficient (c) based on land use coefficient, debit AWLR, and based on SWAT application. Calculation of the coefficient based on land use map until be done by Arcgis method, debit AWLR using Hasper method and SWAT application. Study shown in period between 2009 – 2017, coefficient flow result is in range 0,36 – 0,37. Flow coefficient using AWLR result is in range 0,36 – 0,37, while flow coefficient using SWAT method is 0,25 – 0,36